Adopsi Aplikasi SI APIK pada UMKM di Kota Makassar: Integrasi Techology Acceptance Model dan Regulasi Pemerintah - Fadlia Indasari; Rini Sulistiyanti; Idrawahyuni Idrawahyuni (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The adoption of digital accounting applications has become an important strategy for improving the quality of financial management among Micro, Small, and Medium Enterprises (MSMEs). Despite the increasing availability of digital technologies, the utilization of accounting applications remains relatively limited due to differences in users’ perceptions of benefits and ease of use. The implementation of the Sistem Aplikasi Pencatatan Informasi Keuangan (SI APIK), developed by Bank Indonesia, provides an opportunity to strengthen financial recording practices among MSMEs. This research examines the influence of Perceived Usefulness and Perceived Ease of Use on Intention to Use and their implications for Actual Use of SI APIK among MSMEs in Makassar City. The study also incorporates Government Regulation as a moderating variable to extend the Technology Acceptance Model (TAM) framework. A quantitative approach was employed using survey data collected from 120 MSME actors who had utilized or participated in SI APIK training programs. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that Perceived Usefulness and Perceived Ease of Use significantly enhance Intention to Use, while Intention to Use positively influences Actual Use. However, Government Regulation does not significantly moderate the relationship between Intention to Use and Actual Use. These results suggest that the adoption of SI APIK is primarily driven by users’ perceptions of utility and ease rather than external regulatory support. The findings contribute to the development of TAM in the context of digital accounting adoption among MSMEs and provide practical implications for strengthening digital transformation initiatives..